Basin-Induced Love Waves in the Eastern Part of the Osaka Basin - Irikura, Kojiro; Hatayama, Ken; Iwata, Tomotaka; Matsunami, Koji (Journal of Physics of the Earth, 1995)
Well-developed basin-induced waves with a predominant frequency of about 0.3 Hz were detected as later arrivals of a direct S-wave in seismograms observed in the Osaka basin located in western Honshu, Japan from three deep earthquakes occurring near Japan. The wave type and the secondary source area of the basin-induced waves were examined using a semblance technique and polarization analyses for small aperture array data in the center of the basin. The results well agree with the characteristics of the Love wave such as particle motion perpendicular to a propagation direction and dispersed apparent phase velocities. The arrival direction was evaluated to be almost due east. Seismograms from the east-west linear array crossing the basin show that the observed Love wave propagated from the east to the west after being excited at the eastern edge of the basin by incidence of the direct S-wave. Numerical simulations of two-dimensional SH problems were performed for the east-west cross section models of the Osaka basin subject to incidence of the direct S-wave. The synthetics agree well with the observed Love wave in a predominant frequency and a group velocity.